2018
DOI: 10.1007/s00773-017-0525-z
|View full text |Cite|
|
Sign up to set email alerts
|

Manoeuvrability in adverse conditions: rational criteria and standards

Abstract: The importance of norming manoeuvrability of ships in adverse weather conditions increased after the introduction of EEDI regulations, which raised concerns that manoeuvrability of ships in adverse conditions may become insufficient if EEDI requirements are achieved by simple reduction of the installed engine power. This paper addresses the definition of the required criteria (i.e. ship's abilities, relevant for the considered problem), measures (values quantifying ship's performance with respect to the criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Possibly, this limit can be increased to 15 m/s in headwind conditions. These conditions require ro-ro passenger ships with very good manoeuvring characteristics and redundancy (and duplication of propulsion system) (Shigunov 2018).…”
Section: Inner Berthsmentioning
confidence: 99%
“…Possibly, this limit can be increased to 15 m/s in headwind conditions. These conditions require ro-ro passenger ships with very good manoeuvring characteristics and redundancy (and duplication of propulsion system) (Shigunov 2018).…”
Section: Inner Berthsmentioning
confidence: 99%
“…The 2013 interim minimum power guidelines address tankers and bulk carriers, as these ship types normally have a low design speed (thus relatively low installed power) and are most at risk when optimized for even lower EEDI values. As the scientific problem of maneuverability in waves is highly demanding, further, in-depth research efforts were devoted to the subject to examine the new guidelines as well as to enhance the understanding of the complex problem [4][5][6][7][8]. The most extensive study should be credited to projects SHOPERA and JASNAOE [9], which led to the draft revisions for the 2013 interim guidelines [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…After a ship is launched, tests are conducted in a sea trial to guarantee the maneuverability of the vessel. External disturbances, such as wind and waves, are not considered in the aforementioned criteria, although some studies have shown that these factors have significant effects on the maneuvering performance of a ship (Paroka et al, 2017;Shigunov, 2018). The rudder angle required to maintain a ship's course increases if wind velocity and wave height increase.…”
Section: Introductionmentioning
confidence: 99%